ARE FEMALE LEADERS REALLY HAVE A BALANCED TASK AND RELATIONSHIP LEADERSHIP STYLE? A PROOF FROM THE FEMALE LEADERS IN ENDE-FLORES. - Helena Carolinda Dua Mea, Maria (Jurnal Keuangan dan Bisnis, 2023)
The goal of this study is to assess the level of balance between task-oriented and relationship-oriented leadership in Ende city women leaders or officials who hold important positions in government institutions and BUMDs such as Head of Office, Head of Field, Head of Unit or Division. They are chosen as respondents because they are prominent persons in the organization and lead specific officials in a specific unit, division, or project. This study is quantitative in nature.  We identified 35 women who held crucial and essential roles in Ende city government institutions, particularly in local government offices. Purposive sampling was utilized as the sample approach. Primary data was gathered by distributing a questionnaire containing 20 statements to assess the aspects of task style and relationship style in female leaders in Ende. Each statement's response is scored on a scale of 1 to 5. The questionnaire data were averaged and graded by category to determine the level of task style and relationship style possessed by respondents. The study discovered that 51.42% of female leaders demonstrated task-oriented leadership and balanced relationships, meaning that female leaders who demonstrated task and relationship leadership exceeded those who simply demonstrated task or relationship leadership.